A Study on Nestle Promotion Strategy - Padmalini Singh; Liem Gai Sin; Nur Shafiqah Binti Kama’Aziri; Oh Zi Jian; Nur Amiera Sofea Binti Mohd Azlan; Putri Nur Illya Balkhis Binti Ibrahim; Dave Hoo Sheng; Daisy Mui Hung Kee; Joseph Tan Soo Heng; Liew Siaw Wee; Lim York Ying (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
This study aims to identify the most effective promotional medium used by Nestle. Nestle is the most successful manufacture which processes high quality and nutrition food and beverage to the Malaysians. To inspire consumers to purchase their products, Nestle must transform their promotional strategies frequently. A research will be conducted to collect information from respondent based on different characteristics to identify which is the most effective promotional medium used by Nestle. Through this research, we establish that the most effective promotional medium is Buy 1 Get 1 under sales promotion that helps consumers save more money. We have applied the implication idea to Nestle that can satisfy the customers’ needs and achieve sales target.